“It was Really Hard for Me to Tell”: The Gap between the Child’s Difficulty in Disclosing Sexual Abuse, and their Perception of the Disclosure Recipient’s Response - Gemara, Netanel (Journal of interpersonal violence, 2023)
Disclosure of child sexual abuse (CSA) is essential to its mitigation and the protection of children. Previous studies have greatly contributed to the understanding of disclosure rates both in childhood and adulthood, in addition to delayed disclosure and disclosure barriers. In acknowledging the relevancy of the ecological framework, researchers have illustrated how the various systems in the children’s lives have a role in their decision to disclose the abuse. The current study was designed to delve into the disclosure stories shared by children during their forensic interviews. Fifty children, 30 girls and 20 boys, from diverse communities in the Jewish society in Israel (15 secular, 15 Orthodox and 20 ultra-Orthodox) were forensically interviewed for the first time following CSA. Thematic analysis was carried out on their narratives, focusing on two main themes. The first was the children’s descriptions of their difficulties to disclose, which were embedded in their own perceptions and experiences, their fear of the disclosure recipient’s response, and their dynamic with the perpetrator. The second theme provided a glance into the children’s descriptions of the disclosure recipients’ responses, which highlighted the children’s central experience of loneliness in the context of the abuse. Theoretical and practical ramifications pertaining to these crucial gaps will be discussed. In addition, specific religious-cultural elements raised in relation to the disclosure will be highlighted. Limitations of the study as well as further recommendations and implications will be introduced.